1987
DOI: 10.1021/jo00230a020
|View full text |Cite
|
Sign up to set email alerts
|

Chemical reactivity and configurational properties of cyclopropyl carbanions derived from a silyl sulfonyl substituted cyclopropene

Abstract: 3,3-Dimethyl-l-(p-tolylsulfonyl)-2-(trimethylsilyl)cyclopropene was prepared by the 1,3-dipolar cycloaddition of 2-diazopropane with p-tolyl2-(trimethylsilyl)ethyyl sulfone followed by photoextrusion of nitrogen from the resulting 3H-pyrazole. Treatment of this material with sodium methoxide produced trans-l-methoxy-2-@tolylsulfonyl)-3,3-dimethylcyclopropane. No detectable quantities of the cis isomer were present in the crude reaction mixture. The cyclopropyl carbanion derived from deprotonation of the (metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…As for an interesting example, in 1987, Padwa and co-workers reported an example of Brønsted acid (TsOH) promoted ring-opening reaction of cyclopropenes to afford the corresponding 1,3-diene products in good yields when the b-cationic center is stabilized by the trimethylsilyl group. 116 According to our studies on arylvinylcyclopropene compounds 83, the activation of 83 would be able to provide In the former case, the reaction of oxonium ion 169 generated from acetal and arylvinylcyclopropene 83 followed by intramolecular Friedel-Crafts reaction affords the corresponding product 166. In the latter case, ring-opening of 162 and subsequent intramolecular Friedel-Crafts reaction, addition with oxonium ion generated from aldehyde produces the corresponding aromatic compound 167 or 168 (Scheme 35).…”
Section: Hydrometalation Reactionsmentioning
confidence: 97%
See 2 more Smart Citations
“…As for an interesting example, in 1987, Padwa and co-workers reported an example of Brønsted acid (TsOH) promoted ring-opening reaction of cyclopropenes to afford the corresponding 1,3-diene products in good yields when the b-cationic center is stabilized by the trimethylsilyl group. 116 According to our studies on arylvinylcyclopropene compounds 83, the activation of 83 would be able to provide In the former case, the reaction of oxonium ion 169 generated from acetal and arylvinylcyclopropene 83 followed by intramolecular Friedel-Crafts reaction affords the corresponding product 166. In the latter case, ring-opening of 162 and subsequent intramolecular Friedel-Crafts reaction, addition with oxonium ion generated from aldehyde produces the corresponding aromatic compound 167 or 168 (Scheme 35).…”
Section: Hydrometalation Reactionsmentioning
confidence: 97%
“…116 In 2007, the second report on acid promoted isomerization reaction of cyclopropene was demonstrated by Shi and co-workers. 69 In the presence of various Lewis acids, naphthalenes 255 and indene derivatives 256 could be isolated in moderate to excellent yields from arylvinylcyclopropenes 83.…”
Section: Acid Promotedmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, in 1987, Padwa and co-workers demonstrated that exposure of 3,3-dimethyl-1-(p-tolylsulfonyl)-2-(trimethylsilyl)cyclopropene (15) to a dilute benzene solution of PTSA resulted in the formation of diene 16 in good yield (Scheme 4). 9 Protonation of 15 gives cyclopropyl cation 17 that undergoes ring opening followed by proton loss to give 16. Cyclopropene 15 was the only substrate used for the acid-catalyzed reaction, as the focus of the study was the chemical reactivity of cyclopropyl anions.…”
mentioning
confidence: 99%
“…[4] However, acid-catalyzed reactions of cyclopropenes have been seldom reported. [5] Recently, our group has explored a new kind of highly substituted arylvinylcyclopropenes stabilized by multi-aromatic rings. These interesting arylvinylcyclopropenes tolerate strong bases and weak acids.…”
mentioning
confidence: 99%